Xiphocentronidae (Trichoptera: Psychomyioidea) from the Andean foothills: first species of Machairocentron and Xiphocentron described in the Peruvian Amazon - Albane Vilarino; Frederico F. Salles; Pitágoras C. Bispo (European Journal of Taxonomy, 2023)
Neotropical Xiphocentronidae may have arrived in South America from Central America in the late Miocene or via the Greater Antilles land bridge during the Oligocene. This would give from 10 to 30 Mya of diversification of the family in South America. However, only 11 species were previously known from the Andean foothills. In this study, five new species are described from Peru, four of Xiphocentron (X. ashaninka sp. nov., X. harakbut sp. nov., X. matsigenka sp. nov., X. yine sp. nov.) and one of Machairocentron (M. amahuaca sp. nov.). The new species are most similar to species described from the Yungas of Argentina, and the Pacific dominion of Colombia and Venezuela. The association with species from the Pacific may suggest a species divergences prior to the major Andean uplift and the Amazon basin formation. The spine-like setae on the basal region of the inferior appendage of Xiphocentron were recognized as topologically homologous to the setal brushes on the ventral projection of Caenocentron. Furthermore, based on the morphology of male and female genitalia of Machairocentron, a mating position different from that described for Psychomyiidae is inferred.